2013
DOI: 10.5194/bg-10-4991-2013
|View full text |Cite
|
Sign up to set email alerts
|

Si cycling in a forest biogeosystem – the importance of transient state biogenic Si pools

Abstract: Abstract. The relevance of biological Si cycling for dissolved silica (DSi) export from terrestrial biogeosystems is still in debate. Even in systems showing a high content of weatherable minerals, like Cambisols on volcanic tuff, biogenic Si (BSi) might contribute > 50% to DSi (Gerard et al., 2008). However, the number of biogeosystem studies is rather limited for generalized conclusions. To cover one end of controlling factors on DSi, i.e., weatherable minerals content, we studied a forested site with abs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
109
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 65 publications
10
109
1
1
Order By: Relevance
“…Melzer et al, 2012;Saccone et al, 2007;Sommer et al, 2013). The magnitude overlaps with Si Alk content attributed to tephra, the initial rapid dissolution of clay minerals and/or complete dissolution of nanocrystalline fractions in our experiments (Fig.…”
Section: Implications For Soil Scientistssupporting
confidence: 67%
“…Melzer et al, 2012;Saccone et al, 2007;Sommer et al, 2013). The magnitude overlaps with Si Alk content attributed to tephra, the initial rapid dissolution of clay minerals and/or complete dissolution of nanocrystalline fractions in our experiments (Fig.…”
Section: Implications For Soil Scientistssupporting
confidence: 67%
“…In forested biogeosystems Puppe et al (2015) found high individual numbers of SiO 2 -synthesizing testate amoebae at study sites with low amounts of Si(OH) 4 and vice versa. However, it is unlikely that testate amoebae depleted amounts of Si(OH) 4 at these sites, because corresponding protozoic Si pools are relatively small compared to phytogenic ones Sommer et al, 2013). Regarding vegetation and corresponding phytogenic Si pools, their influence on the amount of Si(OH) 4 in soils has been shown in several studies (e.g., Bartoli, 1983;Farmer et al, 2005;Sommer et al, 2013).…”
Section: Drivers Of Short-term Changes In Water-soluble Si At Chickenmentioning
confidence: 86%
“…On the one hand, dust depositions (dry deposition) at Chicken Creek are very low (73-230 mg m −2 d −1 ) and only slightly above the annual average (70-90 mg m −2 d −1 ) measured in the state of Brandenburg . On the other hand, the total input of Si (as a lithogenic element) from precipitation (wet deposition) is negligible as well (< 1 kg Si ha −1 yr −1 , Sommer et al, 2013).…”
Section: Drivers Of Short-term Changes In Water-soluble Si At Chickenmentioning
confidence: 99%
See 2 more Smart Citations